Zimbabwean mbira music on an international stage : Chartwell Dutiro's life in music - Dutiro, Chartwell; Howard, Keith, 1956- (SOAS musicology series., 2007)
Chartwell Dutiro, an mbira player since childhood and former member of Thomas Mapfumo and the Blacks Unlimited, arrived in Britain in 1994 and has lived there ever since. He works primarily with Zimbabwean and British musicians, and, while allying himself and his music to his Shona ancestors, his music represents both tradition and its transformation. This volume is a collaborative venture between musicians and academics, which builds an account of the mbira, the most important of Zimbabwe's traditional instruments. It celebrates Dutiro's musicianship, exploring his musical development and the.